2023
DOI: 10.3390/cells12081141
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Aberrant β-Catenin Pathway on Cholangiocarcinoma Heterogeneity

Abstract: The poor prognosis of most cases of advanced cholangiocarcinoma (CCA) constitutes a severe problem in modern oncology, which is aggravated by the fact that the incidence of this liver cancer is increasing worldwide and is often diagnosed late, when surgical removal is not feasible. The difficulty of dealing with this deadly tumor is augmented by the heterogeneity of CCA subtypes and the complexity of mechanisms involved in enhanced proliferation, apoptosis avoidance, chemoresistance, invasiveness, and metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 105 publications
1
1
0
Order By: Relevance
“…Our findings demonstrate that a substantial proportion of CRC tumor samples exhibited aberrant β-catenin expression, (82.3%), while a smaller subset of samples displayed membranous β-catenin expression (11.4%). This observation is consistent with previous studies that have highlighted the prominent role of nuclear β-catenin in CRC [ 13 ]. The observed diversity in β-catenin localization suggests heterogeneity within CRC tumors, possibly reflecting different stages of tumor progression and distinct biological behaviors.…”
Section: Discussionsupporting
confidence: 94%
“…Our findings demonstrate that a substantial proportion of CRC tumor samples exhibited aberrant β-catenin expression, (82.3%), while a smaller subset of samples displayed membranous β-catenin expression (11.4%). This observation is consistent with previous studies that have highlighted the prominent role of nuclear β-catenin in CRC [ 13 ]. The observed diversity in β-catenin localization suggests heterogeneity within CRC tumors, possibly reflecting different stages of tumor progression and distinct biological behaviors.…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, whether NKD1 is also involved in the proliferation and migration of PASMCs remains unrevealed. β-catenin serves as the critical regulator of Wnt signaling pathway and plays an important role in adherens junctions and stabilizing cell-cell contacts [17]. It is demonstrated that increased expression of β-catenin is associated with enhanced proliferation, migration of PASMCs [18], an also accelerated development of PAH [19].…”
Section: Introductionmentioning
confidence: 99%